Breastfeeding intention and early post-partum practices among overweight and obese women in Ontario: a selective population-based cohort study. (April 2013) - Visram, Hasina; Finkelstein, Sara A.; Feig, Denice; Walker, Mark; Yasseen, Abdool; Tu, Xiaowen; Keely, Erin
<x xml:space="preserve">Abstract</x> Objective: To explore the relationship between overweight and obesity and breastfeeding behaviors, a cohort study was conducted among 22, 131 women who delivered in Ontario hospitals between April 1 2008 and March 31 2010. Methods: Data regarding maternal characteristics, maternal body mass index (BMI), infant characteristics, and breastfeeding practices were obtained through the Better Outcomes Registry & Network birth records Database. Multivariate linear regression analysis was used to determine the rates of three outcome measures - intention to breastfeed, exclusive breastfeeding in hospital, and exclusive breastfeeding upon discharge from hospital – between non-obese, overweight and obese patients. Results: While overweight mothers have similar intentions to breastfeed compared to non-overweight mothers (OR 1.03 (0.87–1.21), obese mothers were less likely to intend to breastfeed (OR 0.84 (0.70–0.99). Overweight and obese mothers were less likely to exclusively breastfeed in hospital compared to non-overweight mothers (aOR 0.67 (0.60–0.75) and 0.67 (0.60–0.75), respectively), and overweight and obese mothers were less likely to exclusively breastfeed on discharge (aOR 0.68 (0.61–0.76) and 0.68 (0.61–0.76), respectively). Conclusions: This study highlights that while overweight and obese women may benefit more from exclusive breastfeeding compared to non-overweight women, they are less likely to exclusively breastfeed in the immediate post-partum period.